2007
DOI: 10.1152/japplphysiol.00521.2006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves cardiac performance in diabetes: in vivo demonstration with quantitative cine-MRI analyses

Abstract: Loganathan R, Bilgen M, Al-Hafez B, Zhero SV, Alenezy MD, Smirnova IV. Exercise training improves cardiac performance in diabetes: in vivo demonstration with quantitative cine-MRI analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
7
25
0
Order By: Relevance
“…It is also possible that there has been an increase in glucagon secretion in such animals 30 and its counterregulatory action has helped in the maintenance of hyperglycemia. Our results are consistent with those of other studies 7,[11][12][13][14]31 , although these have used different exercise protocols (i.e., treadmill). On the other hand, some studies have shown that exercise was able to improve glucose metabolism in diabetic rats 32,33 .…”
Section: +supporting
confidence: 92%
See 3 more Smart Citations
“…It is also possible that there has been an increase in glucagon secretion in such animals 30 and its counterregulatory action has helped in the maintenance of hyperglycemia. Our results are consistent with those of other studies 7,[11][12][13][14]31 , although these have used different exercise protocols (i.e., treadmill). On the other hand, some studies have shown that exercise was able to improve glucose metabolism in diabetic rats 32,33 .…”
Section: +supporting
confidence: 92%
“…These findings at the cellular level are consistent with the diastolic dysfunctions observed in diabetic hearts in vivo 7,11 .…”
Section: +supporting
confidence: 87%
See 2 more Smart Citations
“…Training was progressively adjusted to achieve 85% of the participant's maximal heart rate (obtained during the VO 2peak test) during aerobic exercise training (weeks 1-4). After that (weeks [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], participants were asked to exercise at the target heart rates of 85% of the maximal heart rate for a minimum of 40 min/session during the aerobic sessions. Participants were instructed to perform at least three sessions a week of aerobic training (combination of treadmill, cycling, and rowing machine with interval training) followed by weekly resistance training (weight training and core exercises) from weeks 1-12.…”
Section: Exercise Trainingmentioning
confidence: 99%